Web-based information system for optimizing non-medical goods requisition - Nadhiroh, Nadhiroh; Nurmiati, Evy (International Journal of Enterprise Modelling, 2025)
The effectiveness of information systems plays a crucial role in enhancing organizational operations, particularly in the management of non-medical goods requisitions in healthcare institutions. At Haji Jakarta Hospital, the previous manual method of managing requisitions led to inefficiencies such as processing delays, data inaccuracies, and difficulties in tracking inventory. This study aims to design and develop a web-based information system to optimize the requisition process for non-medical goods. The research applies the Rapid Application Development (RAD) methodology, which includes requirements planning, design workshop, and implementation phases. Data were gathered through interviews, observations, and document analysis, followed by system modeling using Unified Modeling Language (UML). The system was developed using PHP as the programming language, MySQL as the database, and XAMPP as the development platform. To ensure the functionality of the application, black box testing was conducted, focusing on validating input, process, and output functions. The resulting system provides key features such as real-time requisition tracking, inventory monitoring, and automated reporting. Compared to the previous manual system, the new application enabled hospital staff to process requisitions more quickly and with greater accuracy, reducing average processing time from approximately two days to just a few hours, and minimizing errors caused by repeated manual data entry. All tested system functions performed successfully, improving transparency and documentation in the requisition process. In conclusion, the developed system significantly improves the accuracy, speed, and traceability of requisition processes and can serve as a reference for similar digital transformation initiatives in other healthcare institutions.